2010
DOI: 10.1016/j.ymgme.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

PKHD1 sequence variations in 78 children and adults with autosomal recessive polycystic kidney disease and congenital hepatic fibrosis

Abstract: PKHD1, the gene mutated in autosomal recessive polycystic kidney disease (ARPKD)/Congenital hepatic fibrosis (CHF), is an exceptionally large and complicated gene that consists of 86 exons and has a number of alternatively spliced transcripts. Its longest open reading frame contains 67 exons that encode a 4074 amino acid protein called fibrocystin or polyductin. The phenotypes caused by PKHD1 mutations are similarly complicated, ranging from perinatally-fatal PKD to CHF presenting in adulthood with mild kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 31 publications
4
67
1
3
Order By: Relevance
“…The diagnosis was confirmed in 73 patients by finding at least one PKHD1 variant judged likely to be pathogenic (22). Clinical and mutational data from these 73 patients are presented (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…The diagnosis was confirmed in 73 patients by finding at least one PKHD1 variant judged likely to be pathogenic (22). Clinical and mutational data from these 73 patients are presented (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 92%
“…DNA variant analyses were performed using Sequencher (GeneCodes, Ann Arbor, MI). The pathogenicity of missense variants was evaluated as described (22) using segregation analysis, general population frequencies, three computational prediction tools [Align GVGD (http://agvgd.iarc.fr/agvgd_ input.php); PolyPhen (http://coot.embl.de/PolyPhen); and SNAP (http://cubic.bioc.columbia.edu/services/SNAP)], and the splice variant interpretation software NetGene2 Server (http://www.cbs.dtu.dk/ services/NetGene2).…”
Section: Sequencing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on COACH syndrome have shown gene involvement in MKS3/TMEM67 genes [12,13]. Exome sequencing on patients with Caroli syndrome have shown association with WDR19 mutations [14,15]. While these genes currently do not play a significant role in diagnosing or treating this condition, there may be clinical utility in the future of these genetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, .700 different PKHD1 mutations are known (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The longest open reading frame of PKHD1 comprises 66 exons and encodes a single-transmembrane protein, called polyductin/fibrocystin, which is mainly expressed in the kidney and liver/cholangiocytes (6,7,19).…”
Section: Introductionmentioning
confidence: 99%